“Cameras Help, but Hurt”: The Role and Use of Prison Cameras for Accountability - Inzana, Victoria (Journal of contemporary criminal justice, 2024)
The context of the carceral environment is based on the logic of surveillance and relies on cameras to act as the ever-present eyes of the institution. We explore the investigative roles that cameras play in the institution from the perspective of correctional staff and residents. A qualitative study was conducted in a medium-security institution in the Midwest region of the United States as part of the Prison Research and Innovation Initiative (PRII). The findings are based on semi-structured interviews with people who are incarcerated and correctional staff (including custody and noncustody staff). Upholding accountability was a perceived benefit of reviewing footage from prison cameras during investigations, yet the harms of selective enforcement against the resident population and the perceived misuse of cameras for staff disciplinary actions thwarted the benefits of having and using cameras.